2002
DOI: 10.1051/0004-6361:20020049
|View full text |Cite
|
Sign up to set email alerts
|

UVSTAR observations of Adara (ϵ CMa): 575–1250 Å

Abstract: Abstract. UVSTAR, UltraViolet Spectrograph Telescope for Astronomical Research, operates in the 500-1250Å wave-band at 1 to 3Å resolution. Here we report on the EUV and FUV observations of the B2 II star Adara, the brightest EUV source in the sky, obtained by UVSTAR during the STS 69 and STS 95 missions. The discussion concerns 1) wavelength and flux calibration, 2) short term time variability of selected spectral features, 3) comparison with previous measurements in the EUV band and 4) comparison with model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For example, such a radiation was observed for the star ǫ CMa (B2 II); it was found that the observed EUV flux at λ < 504 Å (He I continuum) is significantly greater than the computed one (Cassinelli et al 1995). Later Gregorio at al. (2002), using both the ATLAS9 model atmospheres of Kurucz (1993) and the spherical model atmospheres of Aufdenberg et al (1999), showed that a more satisfactory agreement with the observed EUV flux for the star ǫ CMa can be achieved; however, the observed flux has a different shape than the predicted one.…”
Section: Discussionmentioning
confidence: 91%
“…For example, such a radiation was observed for the star ǫ CMa (B2 II); it was found that the observed EUV flux at λ < 504 Å (He I continuum) is significantly greater than the computed one (Cassinelli et al 1995). Later Gregorio at al. (2002), using both the ATLAS9 model atmospheres of Kurucz (1993) and the spherical model atmospheres of Aufdenberg et al (1999), showed that a more satisfactory agreement with the observed EUV flux for the star ǫ CMa can be achieved; however, the observed flux has a different shape than the predicted one.…”
Section: Discussionmentioning
confidence: 91%
“…Here the deviations from LTE play a secondary role, with the major contribution from the transition to a spherical, extended atmosphere from a plane geometry. Later, more satisfactory agreement was obtained [22] with the observations on ε CMa; however, although the level of the calculated UV flux agreed better on the average with the observations, the wavelength distributions of the flux in the calculations and the observations were substantially different. In addition, the observed intensities of the spectrum lines in the UV region under consideration were too strong compared to the calculations [22].…”
Section: The Adequacy Of the Models For Stellar Atmospheresmentioning
confidence: 60%
“…The lack of DIBs in HD 52089 is likely due to its short distance and the very low interstellar extinction in its direction. In addition, HD 52089 is not only the hottest star in our sample, but also the strongest ultraviolet source in the night sky [74], which may be able to photodissociate DIB carriers.…”
mentioning
confidence: 97%